Evaluating the effects of dietary glutamine on performance, carcass traits, blood biochemistry, and intestine morphology in laying quail - Ewa Tomaszewska; Kamil Drabik; Kornel Kasperek; Piotr Dobrowolski; Monika Hułas-Stasiak; Renata Pyz-Łukasik; Waldemar Paszkiewicz; Monika Ziomek; Janine Donaldson; Katarzyna Dobrowolska; Artur Burmaczuk; Justyna Batkowska; et al. (Poultry Science)
This study investigated the effects of dietary glutamine (Gln) supplementation on the performance, carcass characteristics, blood biochemistry, intestinal morphology, and gut microbiota of laying quail over a 12-week period, with analyses conducted after 6 and 12 weeks of supplementation. Seven-week-old dual-purpose female quails at the onset of laying were assigned to diets containing 0% (control), 0.5%, 1%, or 1.5% Gln. Performance metrics included laying rate, daily feed intake, and feed efficiency. Supplementation with 0.5% Gln significantly enhanced the laying rate after 12 weeks; daily feed intake and feed efficiency varied over time but were not consistently affected by Gln. Breast muscle weight was highest in quail supplemented with 1.5% Gln after 6 weeks. Blood serum analyses showed that total protein and albumin concentrations were highest in quail receiving 0% and 1% Gln after 12 weeks, while supplementation with 0.5% Gln decreased triacylglycerol levels after 12 weeks. Glucose and creatinine levels varied with Gln supplementation and between the two time points; enzyme activities (alanine transaminase, alkaline phosphatase, and gamma-glutamyl transpeptidase) were affected by both Gln dose and length of supplementation. Intestinal morphology was significantly influenced by Gln dose and supplementation period. The longest villi were observed in quail supplemented with 1% Gln after 6 weeks, decreasing by 12 weeks. The widest villi were recorded in quail receiving 1.5% Gln after 6 weeks, with villus width decreasing over time. Crypt depth varied significantly, with the deepest crypts observed at 6 weeks in quail supplemented with 1% and 1.5% Gln, becoming shallower after 12 weeks. Microbial analysis of digesta samples revealed Lactobacillaceae as the predominant bacterial family, followed by Enterobacteriaceae and genera including Streptococcus and Staphylococcus. Overall, dietary Gln supplementation influenced performance, carcass characteristics, blood biochemical parameters, intestinal morphology, and gut microbiota composition in laying quail, with effects varying between 6 and 12 weeks of supplementation. These findings suggest that Gln supplementation has the potential to enhance quail performance and health over time.